Desenvolvimento de um sistema de monitoramento de vibrações em estruturas de baixa frequência natural - Tozetto, Ricardo Schleder (2016)
The purpose of this work is the development of structure monitoring system based on dynamical measurement data, giving resources for structural verification and retro-analysis requirements. The motivation for this research is the absence of cost-effective effective methods applied on structural evaluation, which has been done based on visual methods – depending of technical ability of the employee – and usually do not able to detect hidden structural failures. For this, a bibliographic review research about modal analysis and structural identification is carry out. Furthermore, an existing device search that realizes the functions of measuring important data for modal analysis and retro-analysis is done. Besides, is defined the methodology of work for the project, verifying the time and resources restrictions. In a second moment, is done the physical project of the electronic device capable of measure the associated variables associated with the operational modal analysis, observing the steps of construction of the sensors, microcontroller and the computational communication. Moreover, laboratory calibration tests are perform in order to grant the reliability of the device, achieving the value of 303 samples per seconds with 16 bits precision in three axis, with 8 range. A field test to validate the device was carried out in a bridge located in Passo Fundo and were compared with recent references.